Amalan psikolinguistik dalam penguasaan sintaksis bahasa Melayu murid Tahun 1 (Jurnal Bahasa, 2007)
The research seeks to identify and examine the psycholinguistics practices that has been instilled and inculcate by the teacher in their teaching methods and could be aquired effectively by the Year 1 pupils. The psycholinguistics experiences enable the Year 1 pupils to understand and acquire the basic Malay (Bahasa Melayu) of syntax level resource materials better. This experimental research based on test and retest were administered on 50 Year 1 pupils of SK Marak in the district of Tumpat, Kelantan. The research findings were obtained from two consecutive tests based on the items contained in the Malay Basic Reading Module. Apart from using the quantitative experimental research, the researcher also used qualitative controlled observational method on all the subjects studied. Survey based on a set of questionnaires were carried on the teachers involved and the subjects studied. Unstructural interviews protocol, were also conducted on the parents and guardians. The data obtained through the achievement records were analyed and studied. The findings on the subjects showed that the subjects enable to acquire the basic reading skills at syntax level better and more effective after instilling the psycholinguistics practices in the teaching and learning methods. The improvement in acquisition of basic reading skills at syntax level was due to the exposition to various psycholinguistics teaching materials, techniques, learning strategies and a systematic teaching and learning approach based on psycholinguistics practices. From the research, we can deduce that the application of psycholinguistics has a very significance influence on the understanding and acquisition of the basic reading skills at syntax level in bahasa Melayu.